2014
DOI: 10.17305/bjbms.2014.2265
|View full text |Cite
|
Sign up to set email alerts
|

Changes in activated partial thromboplastin time and international normalised ratio after on-pump and off-pump surgical revascularization of the heart

Abstract: Surgical revascularization of the heart (CABG - coronary artery bypass grafting) is one way of treating coronary heart disease. Bleeding is one of the serious and frequent complications of heart surgery and can result in increased mortality and morbidity. Hemostasis disorder may be secondary consequences of surgical bleeding, preoperative anticoagulant therapy, and the use of cardiopulmonary bypass. Tests used for routine evaluation of the coagulation system are activated partial thromboplastin time (APTT) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…First, it appears that not only amiodarone injection, but also cardiac surgery can affect the anticoagulant effect of warfarin. Previous studies have suggested that the PT-INR values in patients who underwent cardiac surgeries were increased after surgery compared with the values before surgery [ 22 ]. In our study, although the values of PT-INR/dose were not significantly different between before and after surgery without administration of amiodarone, the status after cardiac surgery individually can be different.…”
Section: Discussionmentioning
confidence: 99%
“…First, it appears that not only amiodarone injection, but also cardiac surgery can affect the anticoagulant effect of warfarin. Previous studies have suggested that the PT-INR values in patients who underwent cardiac surgeries were increased after surgery compared with the values before surgery [ 22 ]. In our study, although the values of PT-INR/dose were not significantly different between before and after surgery without administration of amiodarone, the status after cardiac surgery individually can be different.…”
Section: Discussionmentioning
confidence: 99%
“…The leading cause of death worldwide, especially in ­developed countries, is coronary artery disease (CAD) [ 1 - 4 ]. The etiology of CAD is atherosclerosis, which obstructs coronary arteries that supply oxygen and nutrition to the heart muscle [ 5 ].…”
Section: Introductionmentioning
confidence: 99%